E-MODULE BASED ON RESEARCH-BASED LEARNING (RBL) ON GLOBAL WARMING MATERIAL: E-MODUL BERBASIS RESEARCH BASED LEARNING (RBL) PADA MATERI PEMANASAN GLOBAL - Nurul Fatimah; Hadi Nasbey; Upik Rahma Fitri (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
The use of learning media is crucial as it can influence the learning process of students, one of which is the use of modules. Electronic modules (e-modules) are employed due to their interactive nature, appealing design, and ability to facilitate students' learning process. This study aims to (1) develop an electronic module (e-module) based on Research-Based Learning (RBL) on the topic of global warming, and (2) determine the feasibility of the electronic module (e-module) based on Research- Based Learning (RBL) on the topic of global warming. The research method used in this study is development research utilizing the ADDIE development model. The ADDIE model consists of several stages: Analyze, Design, Develop, Implement, and Evaluate. However, this study will be conducted only up to the Develop stage, or product development. The e-module developed adopts a research-based learning model focusing on the topic of global warming, supplemented with images, videos, and animations that are engaging and accessible from various devices.